The Engineering Properties Of High Strength Heavyweight Concrete Containing Steel Slag Aggregate And Steel Fiber With Nano Material Additives - Khalaf, Mohammed Adil (2021)
There are limited literatures available on the production of high strength heavyweight concrete (HSHWC) with holistic considerations on the water content, aggregate ratios, use of nano additives and mechanical reinforcement with low cost heavy aggregate. The work is aimed to overcome the limitations by establishing a novel approach for developing HSHWC containing steel furnace slag aggregate (SFSA) with very low W/C ratio, optimized volumetric ratio of aggregates, use of nano additives and fiber reinforcements.